The boys ebook A memoir of hollywood and family. - Howard, Ron (2021)
INSTANT NEW YORK TIMES BESTSELLER "This extraordinary book is not only a chronicle of Ron's and Clint's early careers and their wild adventures, but also a primer on so many topics—how an actor prepares, how to survive as a kid working in Hollywood, and how to be the best parents in the world! The Boys will surprise every reader with its humanity." — Tom Hanks "I have read dozens of Hollywood memoirs. But The Boys stands alone. A delightful, warm and fascinating story of a good life in show business." — Malcolm Gladwell Happy Days, The Andy Griffith Show, Gentle Ben—these shows captivated millions of TV viewers in the '60s and '70s. Join award-winning filmmaker Ron Howard and audience-favorite actor Clint Howard as they frankly and fondly share their unusual family story of navigating and surviving life as sibling child actors. "What was it like to grow up on TV?" Ron Howard has been asked this question throughout his adult life. in The Boys, he and his younger brother, Clint, examine their childhoods in detail for the first time. For Ron, playing Opie on The Andy Griffith Show and Richie Cunningham on Happy Days offered fame, joy, and opportunity—but also invited stress and bullying. For Clint, a fast start on such programs as Gentle Ben and Star Trek petered out in adolescence, with some tough consequences and lessons. With the perspective of time and success—Ron as a filmmaker, producer, and Hollywood A-lister, Clint as a busy character actor—the Howard brothers delve deep into an upbringing that seemed normal to them yet was anything but. Their Midwestern parents, Rance and Jean, moved to California to pursue their own showbiz dreams. But it was their young sons who found steady employment as actors. Rance put aside his ego and ambition to become Ron and Clint's teacher, sage, and moral compass. Jean became their loving protector—sometimes over-protector—from the snares and traps of Hollywood. By turns confessional, nostalgic, heartwarming, and harrowing, THE BOYS is a dual narrative that lifts the lid on the Howard brothers' closely held lives. It's the journey of a tight four-person family unit that held fast in an unforgiving business and of two brothers who survived "child-actor syndrome" to become fulfilled adults.